Post-liver transplant HBV infection (Review) - A. D. Nikogosova; D. V. Umrik; O. M. Tsirulnikova (Вестник трансплантологии и искусственных органов)
Chronic hepatitis B virus (HBV) infection is common throughout the world. According to the World Health Organization, about 300 million people around the world are living with the HBV infection markers, with prevalence ranging from 0.4% to 8.5%, depending on the region. Untreated HBV infection results in severe liver disease, including cirrhosis and hepatocellular carcinoma (HCC), in at least one third of patients. While vaccination and new antiviral drugs are effective in preventing the severe consequences of HBV infection, liver transplantation remains the ultimate therapy for patients with HBV in cirrhosis. In patients with HBV replication, recurrence in the graft occurs in 100% of cases, which requires antiviral therapy combined with immunosuppressive therapy. According to the literature, de novo HBV infection after orthotopic liver transplantation (OLTx) in patients without replication and even in patients negative for hepatitis B surface antigen is between 1.7% and 5% [Castells L. et al., 2002]. After OLTx, liver recipients with baseline chronic HBV infection and patients with de novo HBV infection occurring after transplantation are indicated for long-term antiviral therapy.